The Cambridge companion to Wittgenstein - Sluga, Hans D.; Stern, David G. (Cambridge University Press, 1996)
Ludwig Wittgenstein (1889-1951) is one of the most important, influential, and often-cited philosophers of the twentieth century, yet he remains one of its most elusive and least accessible. The essays in this volume address central themes in Wittgenstein's writings on the philosophy of mind, language, logic, and mathematics. They chart the development of his work and clarify the connections between its different stages. The contributors illuminate the character of the whole body of work by keeping a tight focus on some key topics: the style of the philosophy, the conception of grammar contained in it, rule-following, convention, logical necessity, the self, and what Wittgenstein called, in a famous phrase, 'forms of life'.